Identification of extracellular matrix proteins in plasma as a potential biomarker for intervertebral disc degeneration - Nayagam, Sharon Miracle; Ramachandran, Karthik; Selvaraj, Ganesh; Sunmathi, R.; Easwaran, Murugesh; Palraj, Narmatha Devi; Anand K. S., Sri Vijay; Muthurajan, Raveendran; Tangavel, Chitraa; Rajasekaran, S. (European spine journal, 2024)
Purpose Recently, there has been significant focus on extracellular matrix proteolysis due to its importance in the pathological progression of intervertebral disc degeneration (IVDD). The present study investigates the circulating levels of extracellular matrix proteins in the plasma of IVDD and determines their potential relevance as biomarkers in disc degeneration. Methods Global proteomic analysis was performed in the plasma samples of 10 healthy volunteers (HV) and 10 diseased subjects (DS) after depletion of highly abundant proteins such as albumin and IgG. Results We identified 144 and 135 matrix-associated proteins in plasma samples from healthy volunteers (HV) and patients with disc degeneration (DS), respectively. Among these, 49 of the matrix-associated proteins were identical to the proteins found in intervertebral disc (IVD) tissues retrieved from the in-house library. Applying stringent parameters, we selected 28 proteins, with 26 present in DS and 21 in HV. 19 proteins were found common between the groups, two of which—aggrecan (ACAN) and fibulin 1 (FBLN1) - showed statistically significant differences. Specifically, ACAN was up-regulated and FBLN1 was down-regulated in the DS-plasma. In particular, DS-plasma exhibited specific expression of collagen type 2a1 (COL2A1), native to the nucleus pulposus. Conclusion The distinct presence of collagen type 2a1 and the elevated expression of aggrecan in IVDD plasma may serve as the basis for the development of a potential biomarker for monitoring the progression of disc degeneration.